Mindfulness-Based Activities in English Teaching to Reduce Anxiety in Islamic Schools - Imraatus Shalihah (Journal of ELT, Linguistics, and Literature, 2025)
This study explores the integration of mindfulness-based activities in English language teaching (ELT) at an Islamic senior high school in Indonesia. It aims to investigate how such activities influence students’ language anxiety, classroom participation, and overall engagement. Using a qualitative case study design, data were collected through classroom observations, teacher and student interviews, and reflective journals. The findings reveal that mindfulness practices—including guided breathing, reflective journaling, and mindful listening—significantly reduced students’ foreign language anxiety, improved emotional regulation, and fostered greater willingness to communicate. Observations also indicated increased voluntary participation and more supportive peer interactions, particularly through mindful listening, which promoted empathy and reduced fear of judgment. Moreover, the cultural and spiritual alignment of mindfulness with Islamic values such as muhasabah (self-reflection), sabr (patience), and ikhlas (sincerity) enhanced students’ receptivity and deepened engagement. These results suggest that mindfulness not only supports linguistic development but also nurtures resilience, peer empathy, and holistic well-being when contextualized in Islamic educational settings. The study contributes to the growing body of research on affective factors in ELT and provides practical implications for integrating mindfulness into culturally relevant pedagogy.